2015
DOI: 10.1002/cplu.201500070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sorbent Properties of Single‐ and Multiwalled Carbon Nanotubes for Volatile Organic Compounds through Thermal Desorption–Gas Chromatography/Mass Spectrometry

Abstract: Carbon nanotubes (CNTs) possess well‐defined structural and chemical characteristics coupled with a large surface area that makes them ideal as sorbent materials for applications where adsorption processes are required. The adsorption properties of carboxylated derivatives of multiwalled carbon nanotubes (COOH‐MWCNT) and singlewalled carbon nanotubes (COOH‐SWCNT), together with their nonfunctionalized counterparts (MWCNT and SWCNT) for 48 common atmospheric volatile organic compounds (VOCs) were determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…VOCs that were found in the Carbopack X/Tenax multisorbent tube but not in the SWCNT sorbent tube are isopropyl alcohol, isoprene, benzene, nonanal, octanal, hexanal, methyl isobutyl ketone and acetophenone. The results from sampling agree with the functional group trends observed previously during the loading of the VOC standards onto the CNT materials, 24 except for benzene and 1,2,4-trimethylbenzene. The discrepancies between the benzene ratios in sample tubes and in VOC standards tubes were deemed to be an artifact interference error.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…VOCs that were found in the Carbopack X/Tenax multisorbent tube but not in the SWCNT sorbent tube are isopropyl alcohol, isoprene, benzene, nonanal, octanal, hexanal, methyl isobutyl ketone and acetophenone. The results from sampling agree with the functional group trends observed previously during the loading of the VOC standards onto the CNT materials, 24 except for benzene and 1,2,4-trimethylbenzene. The discrepancies between the benzene ratios in sample tubes and in VOC standards tubes were deemed to be an artifact interference error.…”
Section: Resultssupporting
confidence: 88%
“…Thermogravimetric analysis (TGA), Raman spectroscopy and inductively coupled plasma-mass spectrometry (ICP-MS) characterisation of the CNTs have been reported previously. 24 VOC standards used for the analysis were obtained from Sigma-Aldrich (St Louis, USA), Merck (Hohenbrunn, Germany), Alfa Aesar (Heysham, Lancaster, UK) and Fluka (Buchs, Switzerland) with purities not less than 97%, except for the following compounds: 1,2,3-trimethylbenzene (93.9%) from Fluka and methacrolein (95%) from Sigma-Aldrich. The neat chemicals were diluted with the appropriate amount of methanol (Schedelco, Malaysia) to prepare (by serial dilutions) VOC standards solution for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the leukemia can be seen in human exposure to benzene (Smaelnejad et al 2015). Due to benzene toxicity in human health, some of variable methods including adsorption (Smaelnejad et al 2015;Lashaki et al 2016;Gomez et al 2016;Gou and Bahrami Yarahmadi 2019;Ncube et al 2017;Jamshidzadeh and Shirkhanloo 2019;Bagheri Hosseinabadi et al 2019), photo-catalytic oxidation (Palau et al 2012;Weon and Choi 2016;Boulamanti and Philippopoulos 2008;Shang et al 2002), thermal oxidation and bio filtration (Wong et al 2015;Mohamed et al 2016) were used for removal of VOC's or BTEX from air. Among them, the adsorption process based on carbon sorbents (CNTs, NG, NGO) was used to remove VOCs from air.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies showed that the coal temperature is closely related to coal gas desorption. e higher the temperature, the larger the desorption rate [1][2][3][4][5][6][7][8][9][10][11]. Temperature changes during gas adsorption and desorption were tested using a gas outburst simulator [12,13].…”
Section: Introductionmentioning
confidence: 99%